Endogenous Hydrogen Sulfide Enhances Carotid Sinus Baroreceptor Sensitivity by Activating the Transient Receptor Potential Cation Channel Subfamily V Member 1 (TRPV1) Channel. Issue 5 (16th May 2017) - Yu, Wen; Liao, Ying; Huang, Yaqian; Chen, Selena Y.; Sun, Yan; Sun, Chufan; Wu, Yuming; Tang, Chaoshu; Du, Junbao; Jin, Hongfang
Abstract : Background: We aimed to investigate the regulatory effects of hydrogen sulfide (H2 S) on carotid sinus baroreceptor sensitivity and its mechanisms. Methods and Results: Male Wistar‐Kyoto rats and spontaneously hypertensive rats (SHRs) were used in the experiment and were given an H2 S donor or a cystathionine‐β‐synthase inhibitor, hydroxylamine, for 8 weeks. Systolic blood pressure and the cystathionine‐β‐synthase/H2 S pathway in carotid sinus were detected. Carotid sinus baroreceptor sensitivity and the functional curve of the carotid baroreceptor were analyzed using the isolated carotid sinus perfusion technique. Effects of H2 S on transient receptor potential cation channel subfamily V member 1 (TRPV1) expression and S‐sulfhydration were detected. In SHRs, systolic blood pressure was markedly increased, but the cystathionine‐β‐synthase/H2 S pathway in the carotid sinus was downregulated in comparison to that of Wistar‐Kyoto rats. Carotid sinus baroreceptor sensitivity in SHRs was reduced, demonstrated by the right and upward shift of the functional curve of the carotid baroreceptor. Meanwhile, the downregulation of TRPV1 protein was demonstrated in the carotid sinus; however, H2 S reduced systolic blood pressure but enhanced carotid sinus baroreceptor sensitivity in SHRs, along with TRPV1 upregulation in the carotid sinus. In contrast, hydroxylamine significantly increased the systolic blood pressure of Wistar‐Kyoto rats, along with decreased carotid sinus baroreceptor sensitivity and reduced TRPV1 protein expression in the carotid sinus. Furthermore, H2 S‐induced enhancement of carotid sinus baroreceptor sensitivity of SHRs could be amplified by capsaicin but reduced by capsazepine. Moreover, H2 S facilitated S‐sulfhydration of TRPV1 protein in the carotid sinus of SHRs and Wistar‐Kyoto rats. Conclusions: H2 S regulated blood pressure via an increase in TRPV1 protein expression and its activity to enhance carotid sinus baroreceptor sensitivity.